NATURAL REGENERATION DYNAMICS IN CAATINGA TREE SUBMITTED TO FOREST MANAGEMENT - Costa Santos, Ana Flávia; de Paula, Alessandro; Anjos Bittencourt Barreto-Garci, Patrícia Anjos; Martins Corrêa, Michele; Rafaela Bombonatti, Jennifer (Floresta, 2023)
This study aimed to evaluate the natural regeneration dynamics in Caatinga subjected to different forest management practices. The work was carried out in the Contendas do Sincorá National Forest, with the predominant vegetation cover being forested steppe savanna. The study area consisted of fixed plots plotted in 2015. The treatments were: control (Con); clear cutting (CC); selective cutting by minimum diameter at breast height ≥ 5 cm; and selective cutting by species. The phytosociological parameters were estimated for each species. The Shannon-Weaver Diversity Index and the Floristic Expansion Index (FEI) were calculated and the Ward method was used for the floristic similarity analysis. A total of 453 individuals were sampled, distributed in 31 species and five morpho-species. Combretum monetaria was highlighted in all treatments and phytosociological parameters. The similarity dendrogram shows that there is floristic similarity between the years 2015 and 2020. The CC treatment obtained the most species with positive FEI in the period from 2015 to 2017, with a result similar to the other treatments in 2020. It is concluded that there was no statistical difference between treatments in relation to diversity after five years of intervention. Stump regrowth was very important at the beginning of regeneration. The floristic similarity between 2015 and 2020 shows a recovery five years after the experiment installation. Management practices did not have a negative impact on the floristic richness of natural regeneration, demonstrating that the area recovers well even with the interference made in the area. Keywords: Steppe savanna, Floristic Expansion Index, Phytosociology.